2010
DOI: 10.1177/155892501000500301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanosized Colloidal Copper on Cotton Fabric

Abstract: This research deals with the synthesis of nanosized copper as colloidal solution and its application to cotton fabric. Copper nano colloids were prepared by chemical reduction of copper salt using sodium borohydride as reducing agent in presence of trisodium citrate. The size and size distribution of the particles were examined by particle size analyzer and the morphology of the synthesized particles was examined by SEM and AFM techniques. X-ray fluorescence spectroscopy detected the presence of copper in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 6 publications
0
28
0
Order By: Relevance
“…The antimicrobial and antifungal properties of textiles treated with monometallic nanoparticles, such as copper and silver, are well established. In line with this, it has been shown that cotton and cotton/polyester textiles coated with Cu, Ag and Ti film produced total elimination of E. coli and S. aureus from the textile surfaces [52,53]. In our recent work, we characterized novel cotton fabrics coated with dispersions of nanoscaled TiO 2 -1% Fe–N particles prepared by the hydrothermal method which exhibited potent antimicrobial activity against E. coli , P. aeruginosa , and S. aureus [28].…”
Section: Discussionmentioning
confidence: 81%
“…The antimicrobial and antifungal properties of textiles treated with monometallic nanoparticles, such as copper and silver, are well established. In line with this, it has been shown that cotton and cotton/polyester textiles coated with Cu, Ag and Ti film produced total elimination of E. coli and S. aureus from the textile surfaces [52,53]. In our recent work, we characterized novel cotton fabrics coated with dispersions of nanoscaled TiO 2 -1% Fe–N particles prepared by the hydrothermal method which exhibited potent antimicrobial activity against E. coli , P. aeruginosa , and S. aureus [28].…”
Section: Discussionmentioning
confidence: 81%
“…Afterwards, nanoparticles are formed after exposure to reducing agents, as hydrothermal treatments, heat, UV radiation, or chemical agents. As already reported, cellulose is known to hold nanoparaticles silver (He et al, 2003;Pinto et al, 2009;Fernandez et al, 2009) or copper (Mary et al, 2009;Chattopadhyay and Patel, 2010) nanoparticles. In this study, cellulose/copper composites were produced after drying at high temperatures or after chemical reduction.…”
Section: Characterization Of the Cellulose/copper Compositesmentioning
confidence: 85%
“…The immobilized nanoparticles showed antimicrobial potential against E. coli in materials intended for burn/wound dressing. Additionally, cotton fabrics have been impregnated with colloidal copper nanoparticles (Chattopadhyay and Patel, 2010). Colloidal copper nanoparticles were also regularly distributed in chitosan films intended for food packaging applications (Cardenas et al, 2009); copper reinforced the antimicrobial activity of chitosan, and the combination of both antimicrobials was highly effective against Staphylococcus aureus and Salmonella typhimurium.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there exists a great need for antimicrobial cotton textiles that is able to protect against major pathogens. Though AgNPs have been investigated for imparting antimicrobial properties to textiles (Chattopadhyay and Patel, 2010), the antimicrobial behavior of radiolytically formed AgNPs bound to cotton fabrics has not been investigated earlier. This report is one of the first of its kind in which the PVA stabilized radiolytically synthesized AgNPs has been investigated for their antimicrobial behavior when bound to textiles.…”
Section: Introductionmentioning
confidence: 99%